Identifikasi Potensi Kawasan Wisata Alam Bukit Stelling Selili Kota Samarinda - sari, fauzia Bagawat (Journal of Urban and Regional Development Studies, 2024)
Samarinda City has a variety of tourist attractions and spread throughout the sub-district, these attractions include natural attractions Stelling Selili hill, cultural tourism and historical heritage, artificial tourism and shopping tourism. In the Bukit Stelling area located in Selili Village, there is a view with a beautiful natural panoramic view. The potential contained in Bukit Stelling has not been supported by accessibility, the condition of tourist infrastructure facilities and the promotion of information that has not been widely publicized. This research aims to identify the study of tourism potential in the Bukit Stelling Natural Area to be used as a tourist area. The analysis method used is quantitative descriptive method. Based on the analysis of existing conditions, both physical conditions and visitors who come to the Bukit Steling area, it can be concluded that the Bukit Stelling area can be developed to become a tourist area.